2019
DOI: 10.15405/epsbs.2019.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities Of Using Internet Educational Videos For Motivation In Computer Science Education

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Terms such as distributed learning, e-learning, online learning, virtual classes, etc. are used as a synonym for distance education (Dragon, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Terms such as distributed learning, e-learning, online learning, virtual classes, etc. are used as a synonym for distance education (Dragon, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the scientific literature has shown that the problem of the quality of education has become highly relevant since the onset of the pandemic (Chick et al, 2020;Elumalai et al, 2021). Scientists consider various aspects of learning during a pandemic and online learning in general: satisfaction with the online learning process (Chen et al, 2020); adaptation and communication in the digital space (Dorsi et al, 2021;Plass & Pawar, 2020a;2020b;Vanherle, 2021); motivation in online learning environments (Dragon, 2019); new forms of forced online interaction (Bardus, et al, 2021;Nalyvaiko, et al 2021;Plass & Pawar, 2020a;Serhan, 2020); comparison of online and offline learning (Goss et al, 2021); monitoring in higher education (Lane & D'Mello, 2018); risks and prospects of forced distance learning (Neuwirth et al, 2021;Zhu & Liu, 2020); involvement in the learning process (Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%